Relationship between self-reported cognitive and behavioural empathy among medical students. Issue 4 (April 2022) - Klöckner, Christina Cronauer; Gerbase, Margaret W.; Nendaz, Mathieu; Baroffio, Anne; Junod, Noelle Perron
Highlights: The VR-CoDES-P is a useful tool to assess medical students and physicians verbal and nonverbal empathic behaviour. Fourteen percent of medical students' responses to patients' cues and concerns were related to verbal empathy. Compared to students with low JSE-S scores, those with high JSE-S scores did not express more verbal empathy. Students scoring high on the JSE-S tended to obtain higher scores for facial expression. Abstract: Objective: The aim of this study was to explore the relationship between cognitive and behavioural empathy in medical students. Methods: Fourteen 4th year medical students recruited on the basis of their scores on the self-reported Jefferson Scale of Empathy (JSE-S) were divided into two groups: low JSE-S scorers ( n = 8) ( M = 96.75, SD = 10.3) and high JSE-S scorers ( n = 6) ( M = 121.3, SD = 2.94). They were discreetly videotaped while taking history with an incognito standardized patient. Students' behavioural empathy was measured using the Verona Coding System (VR-CoDES-P) and rating of non-verbal behaviour. Results: Patients expressed the same number of concerns per encounter in both groups but gave more cues to high-scorers ( p = 0.029). However, students of both groups demonstrated the same amount of verbal empathy (high: 16% vs low: 15% p = 1.00). High JSE-S scorers' non-verbal communication tended to be rated slightly higher than low JSE-S-scorers with a higher use of facial expression ( p = 0.008). Conclusion: This study did not reveal any differences of students' verbal empathy to patients' cues and concerns between low and high JSE_S scorers. Practice implications: The VR-CoDES_P is a useful tool to assess medical students and physicians empathic behaviour, allowing to disentangle the different components of empathy.